2005
DOI: 10.1073/pnas.0503676102
|View full text |Cite
|
Sign up to set email alerts
|

The SET domain protein Metnase mediates foreign DNA integration and links integration to nonhomologous end-joining repair

Abstract: The molecular mechanism by which foreign DNA integrates into the human genome is poorly understood yet critical to many disease processes, including retroviral infection and carcinogenesis, and to gene therapy. We hypothesized that the mechanism of genomic integration may be similar to transposition in lower organisms. We identified a protein, termed Metnase, that has a SET domain and a transposase͞nuclease domain. Metnase methylates histone H3 lysines 4 and 36, which are associated with open chromatin. Metnas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
343
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(355 citation statements)
references
References 50 publications
10
343
1
Order By: Relevance
“…Metnase contains two functional domains: a SET domain and a Transposase/Integrase domain, which contains a DDE motif that is common to the transposase and retroviral integrase family. We found that Metnase under-expression resulted both in decreased DNA DSB repair by NHEJ and decreased integration of foreign DNA [1]. Genomic integration of lentiviruses such as HIV has three distinct steps.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Metnase contains two functional domains: a SET domain and a Transposase/Integrase domain, which contains a DDE motif that is common to the transposase and retroviral integrase family. We found that Metnase under-expression resulted both in decreased DNA DSB repair by NHEJ and decreased integration of foreign DNA [1]. Genomic integration of lentiviruses such as HIV has three distinct steps.…”
Section: Introductionmentioning
confidence: 87%
“…HEK293 cells were transfected with pcDNA3.1-Metnase or pcDNA3.1 (vector control, Invitrogen, Carlsbad, CA) and selected with G418 for stable over-expression of Metnase as described previously (1). For Metnase under-expression HEK293 cells were transfected with pRNA-U6/hygro-siMET or pRNA-U6/hygro (vector control expressing a scrambled siRNA; Genscript, Piscataway, NJ), selected with hygromycin and individual colonies were screened for Metnase under-expression by reverse transcription-PCR (RT-PCR) [1].…”
Section: Metnase Over-and Under-expressing Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations